Evaluasi Program Management Trainee Incubator 2023 dengan Model Evaluasi Kirkpatrick - Muzakkir, Muhammad; Kartika, Lindawati (Manajemen dan Bisnis, 2025)
This research aims to evaluate the effectiveness of the 2023 Management Trainee Incubator program implementation using Kirkpatrick's evaluation model at the levels of reaction, learning, behavior, and results. This research employs a descriptive quantitative method with a saturated sampling technique. The entire population of 52 program participants was used as the research sample, with primary data derived from program evaluation questionnaires and secondary data sourced from a literature review. Data in this study were analyzed using descriptive statistics, GAP Analysis, and Net Promoter Score (NPS). The findings indicate that at the reaction level, participants' perceptions are in the very high category, at the learning level, there was an increase in participants' knowledge and skills, at the behavior level, participants intended to follow the management trainee program, and at the results level, participants were willing to recommend the program to others